Catalysis and Electron Transfer in De Novo Designed Helical Scaffolds. Issue 20 (2nd March 2020) - Pinter, Tyler B. J.; Koebke, Karl J.; Pecoraro, Vincent L.
Abstract: The relationship between protein structure and function is one of the greatest puzzles within biochemistry. De novo metalloprotein design is a way to wipe the board clean and determine what is required to build in function from the ground up in an unrelated structure. This Review focuses on protein design efforts to create de novo metalloproteins within alpha‐helical scaffolds. Examples of successful designs include those with carbonic anhydrase or nitrite reductase activity by incorporating a ZnHis3 or CuHis3 site, or that recapitulate the spectroscopic properties of unique electron‐transfer sites in cupredoxins (CuHis2 Cys) or rubredoxins (FeCys4 ). This work showcases the versatility of alpha helices as scaffolds for metalloprotein design and the progress that is possible through careful rational design. Our studies cover the invariance of carbonic anhydrase activity with different site positions and scaffolds, refinement of our cupredoxin models, and enhancement of nitrite reductase activity up to 1000‐fold. Abstract : Designer proteins : The de novo design of metalloproteins allows the determination of what is required to build in function in an unrelated protein structure. This Review focuses on protein design efforts to create de novo metalloproteins within alpha‐helical scaffolds; it showcases the versatility of alpha helices as scaffolds for metalloprotein design as well as the progress that is possible through rational design.